Proposing blockchain based framework to mitigate VUCA realm problems for automobile life cycle - Ahmed, Osama; Kamabe, Hiroshi (Frontiers in Blockchain, 2025)
In today’s automotive industry, characterized by demand volatility, process uncertainty, supply chain complexity, and information ambiguity, achieving operational excellence has become increasingly challenging. To address these issues, we propose a novel framework that integrates blockchain technology into the life cycle of an automobile. Specifically, our solution employs Delegated Proof of Stake (DPoS) as a consensus mechanism and utilizes a Private Interplanetary File System (IPFS) for data storage and retrieval. This framework aims to enhance transparency, traceability, and data integrity across all stages of an automobile’s life cycle. We provide a detailed delegate’s election process in DPoS and data storage and retrieval on Private IPFS through sequence diagrams. By mitigating vulnerabilities and reducing uncertainties, our approach improves operational efficiency and stakeholder satisfaction, offering a robust solution to the challenges within the VUCA (volatility, uncertainty, complexity, ambiguity) realm in the automotive industry.